Inhibition of OCTN2-mediated transport of carnitine by etoposide - Hu, C.; Lancaster, C.; Zuo, Zhili; Hu, S.; Chen, Z.; Rubnitz, J.; Baker, S.; Sparreboom, A. (American Association for Cancer Research, 2013)
OCTN2 is a bifunctional transporter that reabsorbs filtered carnitine in a sodium-dependent manner andsecretes organic cations into urine as a proton antiport mechanism. We hypothesized that inhibition of OCTN2 by anticancer drugs can influence carnitine resorption. OCTN2-mediated transport inhibition by anticancer drugs was assessed using cells transfected with human OCTN2 (hOCTN2) or mouse Octn2 (mOctn2).Excretion of carnitine and acetylcarnitine was measured in urine collected from mice and pediatric patients with cancer before and after administration of etoposide. Five of 27 tested drugs (50–100 mmol/L) inhibited hOCTN2-mediated carnitine uptake by 42% to 85% (P < 0.001). Of these inhibitors, etoposide was itself a transported substrate of hOCTN2 and mOctn2. Etoposide uptake by hOCTN2 was reversed in the presence of excess carnitine. This competitive inhibitory mechanism was confirmed in an in silico molecular docking analysis. In addition, etoposide inhibited the transcellular apical-to-basolateral flux of carnitine in kidney cells. Etoposide was also associated with a significant urinary loss of carnitine in mice (1.5-fold) and in patients with cancer (2.4-fold). Collectively, these findings indicate that etoposide can inhibit hOCTN2 function, potentially disturb carnitine homeostasis, and that this phenomenon can contribute to treatment-related toxicities